Soldiers’ Wives’ Resilience as Conceptual Metaphor in Merah Putih Memanggil and Sayap-Sayap Patah - Rahmah, Neneng Farida (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2025)
This research examines the resilience of soldiers' wives as a conceptual metaphor represented in the Indonesian films Merah Putih Memanggil and Sayap-Sayap Patah. The research employs a metaphorical framework to analyse how these films portray the emotional strength, perseverance, and sacrifices of soldiers' wives amidst the hardships they face. The metaphorical representation serves to highlight broader themes of loyalty, endurance, and the unseen struggles within military families. Through the analysis of narrative and visual elements, the study demonstrates how the wives' resilience mirrors the physical and psychological struggles of their husbands, thereby offering a more profound comprehension of their role that challenges conventional stereotypes. The films Merah Putih Memanggil and Sayap-Sayap Patah represent the emotional resilience of soldiers' wives through conceptual metaphors such as “a promise as an emotional contract,” “time as distance,” and “blanket and shroud,” which illustrate the tension between hope and the fear of loss, where these metaphors not only convey the wives’ psychological struggles but also highlight how Indonesian cinema is beginning to provide significant narrative space for women as subjects of emotional experience within military and nationalist contexts.